The Incidence of Systemic Inflammatory Response Syndrome and Urosepsis following Retrograde Intrarenal Surgery (RIRS) in a Tertiary Care Hospital of Kathmandu, Nepal - Batajoo, Rajesh; Yadav, Chandra Shekhar; Kasaju, Atul; Baidya, Jagdish Lal (Nepal Medical College Journal, 2022)
In recent years, the use of retrograde intra renal surgery (RIRS) for the management of nephrolithiasis is on the rise worldwide. It is commonly considered a safe procedure with lesser complications. The current study aimed to study the incidence of systemic inflammatory response syndrome and urosepsis following retrograde intra renal surgery (RIRS). This is the retrospective observational study among 356 patients who underwent RIRS and 52 were readmitted as 36 developed SIRS and 16 developed urosepsis as a complication in last 5 years (July 1st 2016 –June 30th 2021) in department of Urology of B&B hospital, Kathmandu. It is found that only post-operative urine culture had significant association with SIRS with p- value (< 0.00). There was no normality in the data so Mann Whitney U test was applied to test the significant difference in the median values of some quantitative variables between the SIRS and No SIRS group. There was significant difference between the median values of stone volume and duration of fragmentation with p values 0.001 and 0.002 respectively. There was no variables that was found to be associated with urosepsis.